Analisis Faktor Penyebab Kesulitan Belajar pada Pembelajaran Bahasa Jawa Kelas IV SD Negeri Tambangan 02 Kota Semarang - auliya, shindy; Agustina, Nawang Shinta; Qatrunnada, Erinna Shinta; Zahrika, Nazala Aprian; Mafaza, Zahiya Aina; Widodo, Susilo Tri (Jurnal Ilmiah Wahana Pendidikan, 2025)
The purpose of this study was to analyze the factors causing difficulties in learning to write Javanese script in grade IV of SD Negeri Tambangan 02 in the 2025/2026 academic year. This study is a qualitative study using a qualitative descriptive approach. The subjects of this study were teachers and students of grade IV of SD Negeri Tambangan 02. Data collection techniques used were interviews, questionnaires, and documentation. The results of the study showed that students had difficulties in learning Javanese. The importance of learning Javanese in elementary schools is to improve good, polite, and noble communication skills in accordance with the values ​​contained in Javanese culture. Factors causing learning difficulties include environmental factors and learning environments. Efforts that have been made by schools to overcome difficulties in learning Javanese are to use several more innovative, interactive, and contextual learning methods. This study is expected to be a basis for increasing the effectiveness of Javanese language learning in elementary schools.